Henrietta - Lennox, Charlotte 1729-1804 (Eighteenth-century novels by women, 2008)
The heroine of Charlotte Lennox's Henrietta is a young Englishwoman who resists her aunt's pressure to convert to Catholicism and is set adrift in London society. But unlike many of her passive, vulnerable contemporaries in fiction, the admirable Henrietta makes her way in the world relying on her own cleverness, conviction, and wit. -- Amazon.com.